Answer :

Given:-


Take



We know that, Formula



Thus,



We know that, Formula



Thus,





We know that, Formula



Thus,




By rationalisation




(x+1)2 = (1+√3)2


x+1 = ±(1+√3)


x +1 = 1+√3 or x +1 = –1–√3


x = √3 or x = –2 – √3


as given, x > 0


Therefore


x = √3


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers